(untitled) (Current Horticulture, 2024)
Tomato (Lucopersicon esculentum) growers face a miserable problem from thrip (Thrips tabaci), whitefly (Bemisia tabaci) and leaf miner (Liriomyze trifolii) during late- rabi season. There is virtually no effective alternative to tackle the menacing effects of thrips, white fly and leaf miner and the only most common means of controlling infestation is through the use of chemicals. Preference of insects towards specific colour is a much known phenomenon. To understand the preference of colour by the thrip, white fly and leaf miner a study was conducted using different coloured traps (blue, yellow green and black) during late rabi season of 2017. The blue was the strong attractant for thrips, yellow colour for white flies and green colour for leaf miners in tomato crop. This study found that preferred coloured sticky traps as a monitoring tool and an alternative for tomato crop protection is less expensive and hazardous than using chemical pesticides.